Congressional Jet-Setting: Lame Duck Travel and Majority Party Advantage in the House. (2nd April 2016) - Dabros, Matthew S.; Nelson, Andrew P.
Abstract : Opportunism can surface at any point in a congressional career. It is especially likely to arise in the final term of office, when electoral constraints are absent, and, as research has shown, retiring legislators opportunistically prioritize leisure over representational responsibilities. This article explores how the majority party in Congress helps its retiring members to substitute leisure for work. It focuses on official foreign travel, a controversial political perquisite whose consumption is controlled by the majority party and is known to be subject to abuse by retiring and nonretiring incumbents. Using an original dataset spanning the 107th to the 111th Congresses, the article demonstrates that retiring members of the House majority not only travel more than retiring minority members, but also more than nonretiring members of both parties. The study has implications for political opportunism, ethics in government, and majority party advantage in Congress.